Reflections in a broken mirror : a cinematic exploration of Afrikaans theatre post-apartheid, c. 1984–2022 - Fox-Martin, Amber Dawn (Stellenbosch : Stellenbosch University, 2023)
Thesis (MA)--Stellenbosch University, 2023.